Trattamento con etanercept dei soggetti con artrite reumatoide in Italia: considerazioni economiche - Mantovani, Lorenzo G. (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
Rheumatoid arthritis is a chronic inflammatory disease affecting the joints and leading to work disability in half of the patients; its prevalence in Italy is estimated to be around 0,5%. The understanding of the pathophysiology of the disease has lead to the development of biotechnologically-derived drugs, among which anti-TNF-a agents. At the present moment, two of these drugs are available in Italy: etanercept and infliximab. The aim of the present work was to furnish a pharmaco-economical comparison among the two anti- TNF-a agents in Italy. The efficacy of antirheumatic therapies is usually measured in terms of percentage of responders, defined as those patients whose symptoms improve of at least 20, 50 or 70% (ACR20, ACR50, ACR70). A review of the published literature revealed that, according to these accepted parameters, etanercept results superior when infliximab is administered at standard doses, while it is at least as effective as infliximab when the latter is at the highest doses. Although drug acquisition costs are comparable for the two drugs at the suggested regimens, economical evaluations performed in several countries indicate that total treatment costs are lower with etanercept as compared to infliximab, mainly because of differences in the route of administration (subcutaneous vs. slow IV infusion), need for patient monitoring and co-administration of methotrexate with infliximab and days at work gained. Thus, from this preliminary analysis it appears that etanercept dominates infliximab, i.e. it provides better results at a lower cost, but this result needs to be tested and confirmed by prospective economical evaluations.